Performance enhancement of mobile ad hoc network life time using energy efficient techniques - Guruprasath Rengarajan; Nagarajan Ramalingam; Kannadhasan Suriyan (Institute of Advanced Engineering and Science, 2023)
Due to the dynamic topology and limited resources in mobile ad hoc networks (MANETs), multicast routing and quality of service (QoS) provisioning are difficult issues. This study introduces an agent-based QoS routing method that uses fuzzy logic to choose the best route while taking into account a variety of independent QoS indicators, including buffer occupancy rate, remaining mobile node battery capacity, and hop count. On the other hand, finding such pathways requires a lot of work in terms of efficiency and security. This study continues to test the security of weak models, and it has been shown that it may be challenging to accept various sorts of assaults. A distributed approach is given that may be used to determine the best resource distribution at each node. Additionally, the least energy-intensive directed acyclic network network flow is selected from a group using the embedded sleep scheduling algorithm. The process of choosing the flow and allocating the resources for each video frame is adjusted to the characteristics of the network connection channel. Results show that the suggested resource allocation and flow selection algorithms provide considerable performance benefits with minimal optimality gaps at a reasonable computational cost when applied to various network topologies.